Fauna dulceacuícola del Parque Tairona Fauna dulceacuícola del Parque Tairona - Galvis V. Germán (Caldasia)
The fresh waters of the Tairona  park  are inhabited mainly by crustaceans, there is a complete lack of primary fresh water fishes due probably to geographical insulation as commented in the text. It is registered the presence of two marine species, one of which living in mountain streams till a hight of 600 meters. Las aguas dulces del Parque Tairona están habitadas principalmente por crustáceos; hay una total ausencia de peces dulceacuícolas primarios debida, probablemente a circunstancias de aislamiento comentadas en el texto. Se registra la presencia de dos especies de origen marino, una de las cuales vive en corrientes montañosas hasta 600 m de altura.